Successful breastfeeding? Investigating mothers' experiences of infant feeding policies in the United Kingdom - Carrington-Windo, A (2018)
This research investigates how women in the UK experience and navigate infant feeding policies which frame specific infant feeding practices as ‘optimal’ for maternal health and infant health and development. At the centre of the research are policies focussed on practices of exclusive breastfeeding for six months followed by the introduction of complementary foods alongside continued breastfeeding. Execution of these practices is termed ‘successful breastfeeding’ in health education. The thesis examines these policies as a contemporary example of biopolitical governance, aiming to advance understanding of how the attempted regulation of health behaviours such as infant feeding plays out in the daily lives of its subjects. This provides insights into the divergence between policy and practice as well as the potentially adverse effects of infant feeding policy. Ethnographic research was conducted in a community network of breastfeeding support services in Oxford, UK, over a period of twelve months, foregrounding the lived reality of mothers as the subjects of infant feeding governance. The findings indicate that mothers are held responsible for achieving successful breastfeeding according to ‘optimal’ practices, with limited acknowledgement in policy of the multiple factors – both within and beyond a mother’s control – that might prevent them from achieving this standard. Conflicts were identified in what constitutes ‘optimal’ infant feeding, and in how breastfeeding ‘success’ is and can be achieved. Mothers navigate these divergent and often conflicting ontologies of success through pragmatic strategies that enable them to negotiate the discrepant demands of early motherhood. These findings contribute to research that highlights the complexities involved in infant feeding decisions and practices, as well as to research that calls for a more ‘mother-centred’ approach to the promotion of breastfeeding.